Local community’s perception towards ecotourism activities at Bagan Sungai Burung, Bagan Datuk, Perak - Lau, Jia Xin (2019)
The main purpose of this study is to understand local community’s perception towards ecotourism activities at Bagan Sungai Burung, Bagan Datuk, Perak and to identify the factors influencing local community to participate in the development of sustainable ecotourism activities at Bagan Sungai Burung, Bagan Datuk, Perak. The research instruments used were questionnaires and face to face interviews with the head of each village. A total number of 200 local communities were chosen to be the respondent for this study. The study found that majority of the respondents in Bagan Sungai Burung involved in ecotourism activities either as a part timer or a full timer. The reasons for them to involve in ecotourism activities are: gaining new experiences, acquiring better source of income, spending their leisure time and improving skills and interests of individuals. With regard to perception, their agency manager believed that the development of ecotourism activities has positive impacts on their local communities. Overall, from the perspective of agency manager, the ecotourism activities at Bagan Sungai Burung has positive impact and is successful to both tourists and local communities. Nonetheless, collaboration and networking with government and private organizations are still needed to further improve the development of ecotourism activities.